Aplikasi VB untuk Evaluasi Real Option Tambang Nikel PT XYZ Sulawesi Selatan - Zamzam Muhammad Akbar; M. Rahman Ardhiansyah; Sri Widayati (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Nickel price volatility creates significant uncertainty in cash-flow projections and may lead conventional Discounted Cash Flow (DCF) valuation to undervalue managerial flexibility in mining investments. This study evaluates the investment feasibility of a laterite nickel mining project at PT XYZ (South Sulawesi) using DCF and Real Options Analysis (ROA) with Binomial Lattice and Black–Scholes models. The DCF results indicate the project is not financially feasible, yielding a negative Net Present Value (NPV) of IDR –109.78 billion, an Internal Rate of Return (IRR) of 5%, and a Payback Period of 7.58 years. ROA quantifies the value of managerial flexibility under market uncertainty, producing an option value of approximately IDR 62.03 billion using the Binomial Lattice model and IDR 7.136 billion using the Black–Scholes model (values to be aligned with the finalized calculation table). Although the option value adds economic insight, it does not fully offset the negative NPV under the base-case assumptions. Therefore, the recommended strategy is to delay investment until market conditions improve or to reassess the exercise cost structure. This study also implements VBA in Microsoft Excel to automate calculations, improving computational efficiency and reducing input errors. Abstrak. Volatilitas harga nikel menimbulkan ketidakpastian proyeksi arus kas sehingga penilaian investasi menggunakan Discounted Cash Flow (DCF) berpotensi mengabaikan nilai fleksibilitas manajerial. Penelitian ini mengevaluasi kelayakan investasi proyek tambang nikel laterit PT XYZ (Sulawesi Selatan) menggunakan DCF dan Real Options Analysis (ROA) dengan model Binomial Lattice dan Black–Scholes, serta mengotomasi perhitungan menggunakan VBA pada Microsoft Excel. Hasil DCF menunjukkan proyek belum layak secara finansial dengan NPV sebesar –Rp109,78 miliar, IRR 5%, dan Payback Period 7,58 tahun. ROA menghasilkan nilai opsi sekitar Rp62,03 miliar (Binomial Lattice) dan Rp7,136 miliar (Black–Scholes) (akan diseragamkan dengan tabel hasil final). Nilai opsi menunjukkan adanya manfaat fleksibilitas keputusan, namun belum cukup untuk menutup NPV yang negatif pada skenario dasar. Oleh karena itu, strategi yang disarankan adalah menunda pelaksanaan investasi hingga kondisi pasar lebih menguntungkan atau meninjau kembali struktur biaya pelaksanaan investasi. Implementasi VBA mempercepat proses perhitungan, meningkatkan konsistensi hasil, dan mengurangi kesalahan input.